Efecto de la melaza en el cultivo de litopenaeus vannamei como inhibidor de crecimiento de vibrios sp a nivel de estanques - Jaén Cruz, Ana Amparo (2013)
Vibriosis is a bacterial disease responsible for mortality of shrimp, Vibrio species are widely distributed in cultivation facilities worldwide. For this research raised the following research objectives: To establish the effect of molasses as a growth inhibitor of Vibrio sp in shrimp farming ponds level. Determine the dose of molasses applied crop cycle as a growth inhibitor of vibrios sp. This research was conducted in the shrimp of Mr. Oswaldo Aguilar Pesantes located at km. 16 way to Balosa zone 17. Variables to study were: molasses dose applied during the growing season. Microbiological analysis of water and shrimp, and count by plate method determined by colony forming unit. (UFC). The results obtained in this investigation were presented dose reduction vibrios was 100 liters / ha, although in lower proportions. Vibrio parahaemolyticus presence in the pond one to 24 hours after application of molasses with a dose of 100 liters / ha provided better results as the number of dropped considerably Vibrio parahaemolyticus. The variance analysis was performed in this study did not present significant difference in the three ponds. In this work we used, 2 treatments with different doses molasses as organic carbon source, noting that there was no further treatment effect due to abiotic conditions in the environment, which favored the proliferation of vibrios throughout the growing season, especially in the pond two showed higher prevalence of these organisms. Of the treatments used in ponds, we conclude that the doses applied during the growing season, do not satisfy the requirements of heterotrophic bacteria, the same ones that are responsible for maintaining the necessary balance in growing and why there is exclusion pathogenic bacteria (Vibrio sp.)